Pewarisan Sifat Ketahanan Cabai terhadap Infestasi Aphis gossypii Glover (Hemiptera: Aphididae) - Ady Daryanto; Muhamad Syukur; Awang Maharijaya; Purnama Hidayat (Jurnal Hortikultura Indonesia, 2017)
ABSTRACTAphis gossypii Glover is one of the major pests of chili pepper and can cause damage up to 65% when the population is not controlled. The objective of this research was to elucidate the genetic control of resistance inheritance character of chilli (Capsicum annuum L.) to A. gossypii. Set a population of six generations (P1, P2, F1, F2, BCP1, BCP2 was established from a cross between IPB C20 (resistant parent) with IPB C313 (susceptible parent). Choice test based experiments was applied with two aphids per leaf on a five-week-old seedlings. The results showed that based on number of individual aphids per plant, segregation of resistance and susceptibility characters in the F2 fitted to the normal distribution, indicated that resistance controlled by polygenic genes. Subsequently based of scaling test analysis, resistance characteristics based on the number of aphids per plant categorized overdominan against resistant parent and controlled by many genes. Genes effect for controlling resistance to A. gossypii infestation was recessive. Broad-sense heritability was relatively large for the infestation of aphids per plant, aphids per leaf, and winged aphids while the narrow sense heritability relatively very low on the infestation aphids per plant and per leaf, indicated by the dominant variance was greater than additive variance.Keywords: action genes, Capsicum annuum, dominant varience, heritabilityABSTRAKKutudaun Aphis gossypii Glover adalah salah satu hama pengganggu penting dalam produksi tanaman cabai. Saat populasi kutudaun tidak terkendali dapat menyebabkan kerusakan tanaman cabai hingga 65%. Tujuan penelitian ini adalah mempelajari kendali genetik pewarisan sifat ketahanan cabai (Capsicum annuum L.) terhadap infestasi A. gossypii. Set populasi enam generasi (P1, P2, F1, F2, BCP1, BCP2) dibentuk dari persilangan tetua P1 (IPB C20) dengan nilai infestasi rendah dan tetua P2 (IPB C313) yang bernilai infestasi tinggi. Metode skrining yang digunakan adalah choice test. Jumlah kutudaun yang diinfestasikan adalah dua ekor per daun pada bibit berumur lima minggu. Hasil penelitian menunjukkan bahwa karakter ketahanan cabai terhadap infestasi kutudaun berdasarkan jumlah A. gossypii per tanaman ialah tetua rentan overdominan terhadap tetua tahan dan dikendalikan oleh banyak gen. Gen-gen pengendali ketahanan terhadap infestasi A. gossypii adalah resesif. Nilai heritabilitas arti luas tergolong besar untuk infestasi kutudaun per tanaman, kutudaun per daun, dan kutudaun bersayap, sedangkan heritabilitas arti sempit tergolong sangat rendah pada infestasi kutudaun per tanaman dan per daun yang ditunjukkan oleh proposi ragam dominan lebih besar dibandingkan ragam aditif.Kata kunci: aksi gen, Capsicum annuum, heritabilitas, ragam dominan